2019
DOI: 10.4254/wjh.v11.i11.735
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity associated with Garcinia cambogia: A case report

Abstract: BACKGROUNDHerbal supplements (HS) for weight loss are perceived to be “safe” and “natural”, as advertised in ads, however, hepatotoxicity can be associated with consumption of some HS. Use of HS may be missed, as the patient may not report these unless specifically asked about these products, since they are often not thought of as medications with potential side effects or interaction potential.CASE SUMMARYWe reported a case of a 21-year-old female with morbid obesity who presented with abdominal pain for 1 wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…With 11,609 the largest HILI case number was published in 2019 ( Figure 3 ) as a consequence of the ongoing worldwide use of RUCAM for assessing causality in suspected HILI cases ( Table 4 ). In particular, contributing countries were in alphabetical order Australia [ 29 ], Brazil [ 183 ], China [ 48 , 196 , 197 , 198 , 199 , 200 , 201 ], Germany [ 213 , 214 , 215 ], India [ 217 ], Italy [ 222 ], Korea [ 103 ], Spain [ 115 , 117 , 240 , 241 , 242 ], Switzerland [ 244 ], and the US [ 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]. Most of the 11,619 HILI cases published in 2019 were from China [ 48 , 196 ] and Korea [ 103 ], with 6971 cases published by Shen et al [ 48 ], 2019 cases reported by Byeon et al [ 103 ], and 1552 cases provided by Chow et al [ 196 ].…”
Section: Worldwide Publications Of Hili Cases Assessed For Causalimentioning
confidence: 99%
“…With 11,609 the largest HILI case number was published in 2019 ( Figure 3 ) as a consequence of the ongoing worldwide use of RUCAM for assessing causality in suspected HILI cases ( Table 4 ). In particular, contributing countries were in alphabetical order Australia [ 29 ], Brazil [ 183 ], China [ 48 , 196 , 197 , 198 , 199 , 200 , 201 ], Germany [ 213 , 214 , 215 ], India [ 217 ], Italy [ 222 ], Korea [ 103 ], Spain [ 115 , 117 , 240 , 241 , 242 ], Switzerland [ 244 ], and the US [ 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]. Most of the 11,619 HILI cases published in 2019 were from China [ 48 , 196 ] and Korea [ 103 ], with 6971 cases published by Shen et al [ 48 ], 2019 cases reported by Byeon et al [ 103 ], and 1552 cases provided by Chow et al [ 196 ].…”
Section: Worldwide Publications Of Hili Cases Assessed For Causalimentioning
confidence: 99%
“…In spite of this, other authors have reported toxic manifestations, including hepatotoxicity, acute pancreatitis, serotonin toxicity and psychosis after the consumption of Garcinia-containing products (either as an extract containing other components or pure). In 16 of the 21 cases described in Table 2 [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], these adverse effects have occurred after the intake of formulations which contained other ingredients besides Garcinia. One of these formulations is Hydroxycut™.…”
Section: Negative Effects On Healthmentioning
confidence: 99%
“…Although in short term trials GC has been proven as generally safe, it is noteworthy to underline that FDA urged consumers to avoid Hydroxycut, a natural product for weight loss containing GC and a variety of other ingredients, because of the report of twenty-three cases of hepatotoxicity associated with its use in 2009 [232]. Moreover, several hepatoxicity cases have been associated also with the use of pure GC extracts [233][234][235][236][237][238].…”
Section: Garcinia Cambogiamentioning
confidence: 99%